Implementation of Gender Equality in the Workplace in Companies Dominated by Men - Handayani, Pramita; Berliyanti, Dita Oki (International Journal Labs, 2023)
This study aims to be able to deepen and analyze related to gender equality and its impact on sustainability in companies dominated by male workers. Gender equality faces challenges in its implementation. In 2023, Indonesia is recorded to rise to rank 87 in the world ranking of gender equality. The acquisition of this ranking was not very good because behind the ranking, the value of Indonesia's gender implementation turned out to be stagnant at 0.697 points. Indonesia is fortunate because of the decline in the value of gender equality implementation around the world. One of the challenges in implementing gender equality is the opportunity for women to be able to get the opportunity to work and at the same time develop careers. In the world of work, there are two industry groups based on data donated by men. The two industries are mining and manufacturing. Realizing this, several companies in both industries began to implement their gender equality programs. As for being able to achieve the objectives of the research, the research method used is qualitative. Data collection techniques include in-depth interviews, observations, and documentation studies. The results of this study state that gender equality in the company can be reviewed in several parts such as policies, governance, challenges in implementation, employee perceptions, and of course employee commitment to attitudes to implement gender equality. This research also includes suggestions for seeking program development in the company and opens up further research related to gender equality in the future.